Flexibility and Muscle Balance Assessment - Roche, D.
Flexibility is an integral component of an athlete`s physical conditioning. An athlete`s flexibility is influenced by the demands placed on the musculoskeletal system as a result of sport participation and is related to the level and length of involvement. Flexibility is of interest to coaches, health professionals and sport scientists due to the role of flexibility in sports performance, influence on posture and muscle balance, injury prevention and rehabilitation. Assessment of flexibility is an important component of an athlete`s fitness profile as it helps to provide the following: - Ensure an athlete can successfully complete the full range of motion (ROM) required in performing skills and techniques of a particular sport. - Detect any restricted ROM that may adversely affect an athlete`s performance, predispose an athlete to injury and/or occur after injury. - Identify and monitor any changes in flexibility as a result of training and performance. Regular testing provides an opportunity to assess the appropriateness of a training or rehabilitation programme on an athlete`s flexibility. - Examine and predict the performance potential of an individual wishing to compete in a sport that requires extreme flexibility. - Determine the return to sport status of an athlete following injury. Flexibility should not be thought of as an overall body component but rather as being joint specific. An athlete has many joints and some have more movement than others. Static flexibility may be defined as the ROM that is available at a joint, where ROM is the total amount of movement (degrees) through which an articulation`s segments may pass (Kreighbaum and Barthels, 1996). The ROM may be attained actively, where the athlete moves the body part, or passively, where the body part is moved for them. Attempts have also been made to define dynamic flexibility in terms of resistance to the movement of a joint (MacDougall et al., 1991). It has been argued that assessment of dynamic flexibility would be a more valid measurement of an athlete`s flexibility (MacDougall et al., 1991; Wilson, 1997) as it would reproduce the patterns of movement of a sport. Another perceived advantage would be the ability to analyse the range and ease of movement whilst reproducing the type of muscle contraction in the required range for that sport. However, an accepted definition, and valid and reliable tests to measure dynamic flexibility, is yet to be widely endorsed in the literature. For this reason further discussion will be limited to static flexibility testing. The specific demands of a sport should be assessed and applied as the basis for selecting appropriate joints and movements for flexibility testing. Restricted flexibility will reduce the ROM available (Wilson et al., 1992). Subsequently, this may have an adverse affect on speed and endurance as at any given resistance muscles will have a greater workload (Nicholas, 1997). Specific flexibility training has been shown to increase joint ROM (Girouard, 1995). Excessive flexibility, in the absence of adequate muscle control, may also be detrimental to an athlete`s performance and/or predispose to injury. Favourable body mechanics for skill performance will be accomplished by attainment of sport specific flexibility requirements, as opposed to the `more is better` principle. Emphasis should be placed on the achievement and maintenance of sport specific requirements rather than obtaining maximal flexibility in related joints and muscles. For those sports that do not require excessive flexibility, attainment beyond the necessary level may not enhance sport performance. Flexibility results have been described in the literature in terms of hypo-(low), normal or hyper-(high) mobility. The use of this terminology may encourage the belief in athletes that attainment of hypermobility is desirable for enhancing sport performance. For this reason, terminology such as limited, acceptable or excessive may be more appropriate. ROM is a commonly used, noninvasive measure of static flexibility, and is specific to a particular joint. Active and passive ROM testing are frequently used as an assessment of an athletes flexibility (Kendall et al., 1993; MacDougall et al., 1991). Passive ROM testing will allow measurement of the available ROM as limited by passive constraints e.g. joint capsule and connective tissue, but does not assess a muscle/muscle group`s ability to move that body segment. Conversely, active testing indicates a muscle/muscle group`s ability to move the body segment(s) throughout the available ROM but does not differentiate between active or passive restraints. Active testing is a more appropriate form of flexibility testing for the majority of sports as it requires muscle strength and, in addition, the tester is able to observe the quality of movement throughout the ROM available. Joint ROM testing has been widely endorsed in the scientific community as a simple measurement of static flexibility (Bunnermanet et al., 1996; Tyler et al., 1996). A number of measurement techniques have been developed and attempts to validate protocols and relate testing to sport performance have been made (Ekstrand and Gillquist, 1982; Ekstrand et al., 1982). Despite a prevalence of articles there is little information available with which to ascertain the required angular displacement of joints during sport specific skills and establish testing protocols that are accepted amongst all interest groups. Therefore, comparison of flexibility testing results with established norms is difficult due to the paucity of information available on sport specific flexibility data for athletes. Throughout the literature little consideration has been paid to the complexity of variables that influence flexibility and, in turn, testing and results. The shape of its articular surfaces and soft tissue structures determines the ROM of a joint. These include the joint capsule, skin, and connective and muscle tissue and in turn may be influenced by age, gender, temperature, current/past type and level of activity, and current or pre-existing musculoskeletal injuries. Muscle length is an important determining factor of an athlete`s flexibility. Joint ROM testing per se fails to identify the influence of muscle length, or change in muscle length, on flexibility. Onejoint muscles should be able to lengthen sufficiently to allow full ROM of the joint they cross. Twojoint and multi-joint muscles allow full ROM of one of the joints they cross if they are not lengthened over the other joint(s). However, these muscles generally do not permit simultaneous full ROM of all joints they cross due to lack of extensibility e.g. hamstring muscle length does not permit simultaneous attainment of full hip flexion and knee extension. Following joint ROM measurement it may be desirable to assess the length of muscles that cross and move the joint(s)1.Handedness influences our movement patterns and musculoskeletal development in sport participation and in activities of daily living. Therefore, left and right side comparison will provide a useful tool in determining the influence of training effects, injury or disuse on an athlete, and in predicting their return to sport ability.